The differing responses of central carbon cycle metabolism in male and female Sargassum thunbergii to ultraviolet-B radiation - Sun, Yan; Zang, Yu; Chen, Jun; Shang, Shuai; Wang, Jing; Liu, Qian; Tang, Xuexi (Frontiers in Plant Science, 2022)
The enhancement of ultraviolet-B radiation (UV-B) radiation reaching the Earth’s surface due to ozone layer depletion is an important topic. Macroalgal species growing in the intertidal zone are often directly exposed to UV-B radiation periodically as the tide changes. In order to better understand the response of macroalgae to UV-B stressed condition, we studied the dominant dioecious intertidal macroalgae Sargassum thunbergii. After consecutive UV-B radiation treatments, we used metabonomics models to analyze and compare the maximum photosynthetic electron transport rate (ETRmax), central carbon cycle metabolism (CCCM) gene expression level, CCCM enzymic activities [pyruvate dehydrogenase and citrate synthase (PDH and CS)], and carbon-based metabolite (including pyruvate, soluble sugar, total amino acid, and lipids) content in male and female S. thunbergii. The results showed that under low and high UV-B radiation, the ETRmax values and six targeted CCCM gene expression levels were significantly higher in males than in females. Under high UV-B radiation, only the CS activity was significantly higher in males than in females. There was no significant difference in PDH activity between males and females. The CCCM models constructed using the metabonomics analysis demonstrate that S. thunbergii males and females exhibit obvious gender differences in their responses to UV-B radiation, which providing us a new understanding to the macroalgal gender differences under UV-B radiation and past investigations always underestimated their diecious characteristics.